SOSIALISASI PENCEGAHAN COVID-19 MELALUI PENERAPAN 5M DI PASAR TRADISIONAL HALAT MEDAN - Mayang Sari Ayu; Dewi Pangestuti; Meri Susanti (Jurnal Pengabdian Mitra Masyarakat, 2022)
World Health Organization (WHO) ) declared Corona Virus Disease 2019 (COVID-19) as a pandemic or world emergency, because COVID-19 cases continue to increase and spread every day. ssince it was discovered at the end of 2019 all over the world including Indonesia. One of the locations and community groups that are vulnerable to COVID-19 transmission is in the traditional market. A place where many people gather, the layout or location of the traditional market is narrow and not well organized. Unhealthy air ventilation, the distance between traders is very close so it looks crowded, the duration of daily contact between traders and buyers often occurs very close. The Faculty of Medicine at the Islamic University of North Sumatra (FK UISU) has a concern for helping the government in preventing the transmission of COVID-19 in community service activities. The academic community chooses the location of activities at the Halat Market Traditional Market, Medan City by providing personal protective equipment (PPE) such as distributing masks, face shields and gloves. This implementation is carried out with counseling about COVID-19 and the application of the 5M health protocol. The time of the activity was on September 9-10 2020. This activity received support from various parties, especially urban villages and traders. Through this activity, it is hoped that traditional markets will not become clusters of transmission of COVID-19 cases.